A new link between stress response and nucleolar function during pollen development in Arabidopsis mediated by AtREN1 protein - Reňák, David; Gibalová, Antónia; Solcová, Katarzyna; Honys, David (Plant, cell and environment, 2014)
Heat shock transcription factors (Hsfs) are involved in multiple aspects of stress response and plant growth. However, their role during male gametophyte development is largely unknown, although the generative phase is the most sensitive and critical period in the plant life cycle. Based on a wide screen of T-DNA mutant lines, we identified the atren1 mutation (restricted to nucleolus1) in early male gametophytic gene At1g77570, which has the closest homology to HSFA5 gene, the member of a heat shock transcription factor (HSF) gene family. The mutation causes multiple defects in male gametophyte development in both structure and function. Because the mutation disrupts an early acting (AtREN1) gene, these pollen phenotype abnormalities appear from bicellular pollen stage to pollen maturation. Moreover, the consequent progamic phase is compromised as well as documented by pollen germination defects and limited transmission via male gametophyte. In addition, atren1/- plants are defective in heat stress (HS) response and produce notably higher proportion of aberrant pollen grains. AtREN1 protein is targeted specifically to the nucleolus that, together with the increased size of the nucleolus in atren1 pollen, suggests that it is likely to be involved in ribosomal RNA biogenesis or other nucleolar functions.
Keywords: Alleles; vývojová regulace genové exprese; Arabidopsis; exony; Gene Expression Regulation, Developmental; penetrance; Cell Nucleolus; klíčení; Phenotype; Chromosome Segregation; transport proteinů; Protein Transport; DNA bakterií; buněčné jadérko; DNA-Binding Proteins; mutace; DNA vazebné proteiny; Genetic Complementation Test; testy genetické komplementace; Exons; Penetrance; zelené fluorescenční proteiny; alely; Germination; reakce na tepelný šok; fenotyp; Mutation; Gene Expression Regulation, Plant; Heat-Shock Response; segregace chromozomů; pyl; Pollen; Green Fluorescent Proteins; proteiny huseníčku; Pollen Tube; regulace genové exprese u rostlin; pylová láčka; DNA, Bacterial; Arabidopsis Proteins